Theorem elb1S | index | src |

theorem elb1S (a b: nat): $ suc a e. b1 b <-> a e. b $;
StepHypRefExpression
2
suc a e. b1 b <-> suc a = 0 \/ suc a - 1 e. b
6
suc a != 0
7
conv ne
~suc a = 0
8
suc a = 0 \/ suc a - 1 e. b <-> suc a - 1 e. b
11
suc a - 1 = a
12
suc a - 1 e. b <-> a e. b
13
8, 12
suc a = 0 \/ suc a - 1 e. b <-> a e. b
14
2, 13
suc a e. b1 b <-> a e. b

Axiom use

axs_prop_calc (ax_1, ax_2, ax_3, ax_mp, itru), axs_pred_calc (ax_gen, ax_4, ax_5, ax_6, ax_7, ax_10, ax_11, ax_12), axs_set (elab, ax_8), axs_the (theid, the0), axs_peano (peano1, peano2, peano5, addeq, muleq, add0, addS, mul0, mulS)